2021
DOI: 10.1038/s41598-021-92990-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the post-treatment therapeutic effect of pinaverium in irritable bowel syndrome: a randomized controlled trial

Abstract: Irritable bowel syndrome (IBS) is the most common gastrointestinal disorder significantly decreasing patients’ lives of quality and placing huge economic burden on our society. Existing studies indicated that the therapeutic effects maintained for a period of time after the treatments were discontinued. It is clinically important to assess these post-treatment therapeutic effects (PTTE), which prevent IBS from relapsing. To assess the PTTE in pinaverium treatment and obtain high-quality evidence to justify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…It can also prevent excessive contraction of intestinal smooth muscle, improve intestinal sensitivity, and increase intestinal peristalsis, thus alleviating discomfort such as abdominal pain. 18 The results of the present study suggested that pinaverium bromide tablets can effectively improve the gastrointestinal microenvironment and relieve the symptoms of abdominal pain and abnormal defecation, with definite efficacy on IBS and few side effects. According to Bor et al 19 , Pinaverium is superior to placebo for the treatment of IBS symptoms, irrespective of patient age or gender, study publication year, sample size.…”
Section: Discussionmentioning
confidence: 53%
“…It can also prevent excessive contraction of intestinal smooth muscle, improve intestinal sensitivity, and increase intestinal peristalsis, thus alleviating discomfort such as abdominal pain. 18 The results of the present study suggested that pinaverium bromide tablets can effectively improve the gastrointestinal microenvironment and relieve the symptoms of abdominal pain and abnormal defecation, with definite efficacy on IBS and few side effects. According to Bor et al 19 , Pinaverium is superior to placebo for the treatment of IBS symptoms, irrespective of patient age or gender, study publication year, sample size.…”
Section: Discussionmentioning
confidence: 53%